Literasi Keuangan Bagi Karyawan Generasi Z - Rotua Simamora, Elisabeth; Situmorang, Adolf; Aditya Pardiyanto, Martinus (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
Generation Z, comprising individuals born from the mid-1990s to the early 2010s, bears increasing responsibility in managing their finances to achieve robust financial goals. Knowledge of good financial management is a key factor in ensuring the sustainability of financial well-being in the future. Recognizing that financial choices made at a young age will have long-term impacts, Generation Z is tasked with the crucial responsibility of understanding the concepts of savings, investments, and wise expenditures. The objective of the PKM is to provide education for young employees to effectively manage their finances. This activity will be conducted by the UMS Faculty Team through lectures and discussions with young employees, the Gen Z. With a better understanding of financial management, Generation Z employees can steer clear of financial pitfalls and attain better financial well-being in the future